Studi Empirik Interaksi Strategis Pemerintah Daerah di Indonesia - Al Husna, Nizza; Yudhistira, Muhammad Halley (Jurnal Ekonomi Kuantitatif Terapan, 2017)
One potential positive impact of fiscal decentralization in Indonesia is positive competition among subnational government to maximize the public welfare. The competition is reflected by spatial correlation of the expenditure per capita with its neighbouring subnational government.  Using the dataset in 2010 at district level and spatial econometrics approach, this study tests whether strategic interaction between region government expenditure is present. Our estimation results show positive strategic interaction among subnational government expenditure.  Furthermore, the highest interaction is for the expenditure in economic, indicating the competition is much more motivated by economic outcomes.